2000
DOI: 10.1046/j.1471-4159.2000.0742497.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Release in the Hippocampus in the Kindling Model of Epilepsy

Abstract: Somatostatin biosynthesis in the hippocampus is activated during and following kindling epileptogenesis. The aim of this study was to investigate whether this phenomenon is associated with enhanced somatostatin release in vivo. Experiments have been run in awake, freely moving rats, implanted with a bipolar electrode in the right amygdala (for kindling stimulation), and with a recording electrode and a microdialysis probe in the left hippocampus. Basal somatostatin-like immunoreactivity (-LI) release was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Baseline and K+ -induced SST release was significantly higher in hippocampal slices kindled rats vs. control rats (Vezzani et al, 1992). An in vivo study microdialysis study reported similar findings, i.e., an increase in both basal and K+ -stimulated release in hippocampus after kindling (Marti et al, 2000). Increased SST release following seizures would likely be protective (see below).…”
Section: Sst Release and Expression Is Upregulated By Seizuresmentioning
confidence: 70%
“…Baseline and K+ -induced SST release was significantly higher in hippocampal slices kindled rats vs. control rats (Vezzani et al, 1992). An in vivo study microdialysis study reported similar findings, i.e., an increase in both basal and K+ -stimulated release in hippocampus after kindling (Marti et al, 2000). Increased SST release following seizures would likely be protective (see below).…”
Section: Sst Release and Expression Is Upregulated By Seizuresmentioning
confidence: 70%
“…The cell bodies and horizontal dendrites of O-LM cells are located in the stratum oriens and provide inhibition to the distal dendrites of pyramidal cells in the stratum lacunosum-moleculare [34]. Somatostatin is released from hippocampal neurons after seizures [35] and its expression was enhanced by seizures in animal models [36]. However, a loss of somatostatin interneurons was found in the hilus in human temporal lobe epilepsy and in animal models of epilepsy while somatostatin usually remained in the Ammon´s horn even in sclerotic hippocampus [37,38].…”
Section: Somatostatinmentioning
confidence: 99%
“…Because NOS and SS colocalize in the dentate hilus of rat hippocampus (Dun et al, 1994), and because the permissive role of NO on SS release are documented (Aguila, 1994;McCann et al, 1996), the behavioral effect of SS would be expected to be inversely related to NOS inhibition. In awake, freely moving rats, kindling epileptogenesis evoked WDS and SS release (Marti, Bregola, Morari, Gemignani, & Simonato, 2000), suggesting a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 93%